An experimental study of the forces on vertical cylinders for an offshore floating photovoltaic energy structure (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Floating Photovoltaic (FPV) energy has already been used on water bodies such as lakes or reservoirs, but the offshore environment conditions are an economical and technical challenge. Nevertheless, the offshore market offers advantages in land use and options for hybrid solutions with other offshore energy sources like wind or wave energy. This innovative energy harnessing option, still in earlier stages compared to the rest of offshore energy sources, could help in achieving the decarbonisation goals. Therefore, in this study, an experimental determination of the forces produced by regular and irregular waves is done on a vertical cylinder that represents a column of a floating offshore solar energy platform.The experiments have been carried out in the wave flume (25 [m] long, 0.6 [m] width and 0.7 [m] height) of the Energy Engineering Department at the Bilbao School of Engineering (University of the Basque Country) at a depth of 0.5 [m] in order to ensure deep-water conditions. Several configurations of waves (heights, H [m], from 0.02 to 0.12 and periods, T [s], between 0.60 and 1.75), cylinders (diameters, D [m], from 0.020 to 0.050) and draughts (d, [m], from 0.5 to 2.0 times the diameter and currents) are used in order to cover a broad range of experimental conditions. In addition, the same experiments have been developed using two consecutive cylinders in order to analyse the wake effect generated by the flow disturbance of the first one. For these experiments, the distance between the centres of the cylinders is varied from 0.05 [m] to 0.50 [m].The waves are generated using a piston type wave maker, controlled by a commercial software, equipped with an active absorption system of reflected waves. The forces are measured through a 6 DOF sensor (Miniature 6-axis force torque sensor, MMS101). The analysis of the results is focused on the wave direction horizontal forces and the experimental values are compared with the theoretical Morison equation’s results.The results will allow to obtain the loads the floating platform will undergo. It will also permit to know more accurately what the drag and inertia coefficients are under different wave conditions, how the parameters of the cylinder affect the loads and how the distance between different columns of the floating platform affects the wake effect and its importance on the loads. In the Figure 1 it is shown one of the results obtained with a good compliance between experimental and theoretical results. It is the case for a cylinder of 50 mm diameter and 50 mm draught under regular waves of H = 0.05 m and T = 0.894 s. In the Figure 2 it is shown the configuration of the experiments in the wave flume.